Aboriginal Homelessness: A Framework for Best Practice in the Context of Structural Violence - Nelly D. Oelke; Wilfreda E. Thurston; David Turner (International Indigenous Policy Journal, 2016)
Homelessness among Indigenous peoples is an important issue in Canada and internationally. Research was conducted in seven metropolitan areas in the four western provinces of Canada to explore current services with the aim of developing a best practices framework to end homelessness for Aboriginal peoples. Sequential mixed methods were used. Key results found agreement that Aboriginal peoples were overrepresented among the homeless and policy determined the approach to and comprehensiveness of services provided. Funding, lack of time, and lack of resources were highlighted as issues. Gaps identified included a lack of partnership, cross-cultural collaboration, cultural safety, and evaluation and research in service provision. Best practices included ensuring cultural safety, fostering partnerships among agencies, implementing Aboriginal governance, ensuring adequate and sustainable funding, equitable employment of Aboriginal staff, incorporating cultural reconnection, and undertaking research and evaluation to guide policy and practices related to homelessness among Aboriginal peoples.